2015
DOI: 10.3109/10428194.2015.1041388
|View full text |Cite
|
Sign up to set email alerts
|

High serum concentration of L-kynurenine predicts unfavorable outcomes in patients with acute myeloid leukemia

Abstract: The immunomodulatory effects of indoleamine 2,3-dioxygenase (IDO) are ascribed to its ability to catalyze the breakdown of the L-tryptophan along the L-kynurenine pathway. Because blasts from patients with acute myeloid leukemia (AML) express IDO, the goal of this study was to investigate the role of L-kynurenine as a prognostic marker for AML. We enrolled 48 AML patients. L-kynurenine concentrations were measured by high-performance liquid chromatography. The median serum L-kynurenine level was 1.67 μM. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Recently it was reported that galectin-9 induces interferon-gamma (IFN-γ) release from NK cells ( Gleason et al, 2012 ). IFN-γ interacts with AML cells inducing the activity of indoleamine 2,3-dioxygenase (IDO1), an enzyme which converts L-tryptophan into formyl-L-kynurenine, which is then converted into L-kynurenine and released ( Corm et al, 2009 , Folgiero et al, 2015 , Mabuchi et al, 2016 ). L-kynurenine affects the ability of NK cells to kill AML cells, an effect which was seen in our experiments and presented in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was reported that galectin-9 induces interferon-gamma (IFN-γ) release from NK cells ( Gleason et al, 2012 ). IFN-γ interacts with AML cells inducing the activity of indoleamine 2,3-dioxygenase (IDO1), an enzyme which converts L-tryptophan into formyl-L-kynurenine, which is then converted into L-kynurenine and released ( Corm et al, 2009 , Folgiero et al, 2015 , Mabuchi et al, 2016 ). L-kynurenine affects the ability of NK cells to kill AML cells, an effect which was seen in our experiments and presented in Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence pointing to a potential role for IDO in AML. First, elevated systemic levels of kynurenine are detectable in patients with AML and have been shown to negatively correlate with overall survival in patients with intermediate risk disease ( 62 , 63 ). IDO has been measured directly in AML blasts both constitutively and after exposure to IFNγ, indicating that the tumor itself may be responsible for the observed systemic kynurenine levels ( 64 , 65 ).…”
Section: Mechanisms Of T Cell Dysfunction In Amlmentioning
confidence: 99%
“…IDO overexpression is correlated with poor clinical outcome in patients with ovarian, endometrial, and colorectal carcinomas [ 13 , 14 ]. We have previously reported that IDO expression in tumor cells and the serum concentration of kynurenine in patients with diffuse large B-cell lymphoma [ 15 17 ], or with acute myeloid leukemia [ 18 , 19 ] are useful prognostic factors. On the other hand, several preclinical studies have demonstrated that IDO inhibitors, such as 1-methyl-tryptophan (1-MT), are therapeutically beneficial for inhibition of cancer cell growth, especially when they are combined with different types of cytotoxic chemotherapeutic agents [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%